Kinetic Parameter Estimation in Alkylation of Benzene with 1-Decene through Hybrid Particle Swarm Optimization - Mohd Zulkefle, Nurul Farihah (UNIVERSITI TEKNOLOGI PETRONAS, 2012)
In this project, a kinetic model for alkylation of benzene with 1-decene over acid catalyst is presented. The desirable product from this alkylation process is 2- phenyldecane which is formed via double bond isomerization and aromatic alkylation reaction. 2-phenyldecane is formed by alkylation of benzene with alkylcarbenium ion. Alkylcarbenium ions are produced from protonation and deprotonation reaction of 1- decene isomers. In this reaction, kinetic constants follow Arhenius equation. Preexponantial factors of the elementary step were calculated from first principle. Activation energies of elementary steps were estimated by using Hybrid Particle Swarm Optimization (HPSO) algorithm. Parameter estimation was performed by varying the initial guess of PSO algorithm which will conduct global search of the parameters. Afterwards, the solution obtained using PSO algorithm is given as initial guesses to the Levenberg–Marquardt algorithm to determine the improved optimal solution. Parameter estimation was carried out using simulated data and the activation energies are constant with the assumed values.